1988
DOI: 10.1016/s0006-3495(88)83150-3
|View full text |Cite
|
Sign up to set email alerts
|

Low conductance gramicidin A channels are head-to-head dimers of beta 6.3-helices

Abstract: Weakly conductive, atypical channels were observed to form from highly purified Val1-gramicidin A in planar lipid bilayer membranes. The structure of these low-conductance channels (minis) was investigated by a detailed study of their channel forming characteristics. The possibility that minis originate from primary structural analogs or degradation products of gramicidin was considered and ruled out. In particular, spontaneous conductance changes in single channels demonstrated that minis can derive directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
6
25
1
Order By: Relevance
“…Single-channel conductance studies have revealed that there are various low-conductance channel states in addition to the major high-conductance states (Busath & Szabo, 1981). Such low-conductance channels convert reversibly to the major channels and are suggested to differ from the major channels in side-chain conformations (Urry et al, 1981;Busath & Szabo, 1988). The present models for the tryptophan conformations do not exclude the possibility that other tryptophan conformations are taken in some low-conductance states.…”
Section: Discussioncontrasting
confidence: 57%
“…Single-channel conductance studies have revealed that there are various low-conductance channel states in addition to the major high-conductance states (Busath & Szabo, 1981). Such low-conductance channels convert reversibly to the major channels and are suggested to differ from the major channels in side-chain conformations (Urry et al, 1981;Busath & Szabo, 1988). The present models for the tryptophan conformations do not exclude the possibility that other tryptophan conformations are taken in some low-conductance states.…”
Section: Discussioncontrasting
confidence: 57%
“…That these amiloride-sensitive channels expressed in oocytes are ENaCs is supported by the fact that they were never observed in water-injected oocytes. We conclude, therefore, that the microenvironment in which ENaC resides determines in large measure its conductance and mean open and closed times (31)(32)(33). Aside from these changes, the channels displayed comparable amiloride sensitivities, ion selectivities, and gating patterns.…”
Section: Discussionmentioning
confidence: 75%
“…We also find sensitivity to batch variability in lipids, especially DOPC. Below the miscibility transition, membranes demonstrate limited stability, and the emergence of large numbers of low conductance “mini-channels” 26 precludes long recordings and makes analysis difficult. Nonetheless, the presence of two separate lifetime distributions persists at temperatures below the miscibility transition.…”
Section: Resultsmentioning
confidence: 99%